Pengetahuan, Sikap, dan Praktik Staf Medis ICU terhadap Perawatan Gizi dan Dampaknya terhadap Pemulihan Pasien di Taiz, Yaman: Knowledge, Attitudes, and Practices of ICU Medical Staff toward Nutrition Care and its Impact on Patient Recovery in Taiz, Yemen - Mohammed, Haitham T. S.; Ali, Lamia A. S.; Saif, Malak Anwar; Al-Adeemy, Nada Khalid; Al-Nadhary, Noha Kamel; Saif, Raghad Sameer; Al-Nadhary, Shaima Kamel; Al-Dobai, Yomna Mukarram; Sari, Nur Mufida Wulan (Universitas Airlangga, 2024)
Background: Proper nutrition is essential for enhancing patient recovery, especially within hospital environments. ICU medical staff are instrumental in providing appropriate nutritional care, which significantly affects patients' health outcomes. However, in Yemen, the lack of knowledge for assessing nutritional requirements, and the importance of nutrients adequacy for patients underscores the importance of improving staff involvement in nutrition care quality management. Objectives: The study aimed to determine the nutritional Knowledge, Attitude, and Practice (KAP) of medical staff in the Intensive Care Unit (ICU) in ninth selected hospitals in Taiz City. Methods: This study used a descriptive cross-sectional design in both governmental and non-governmental hospitals from March 1st,2024 to August 10th,2024. The medical staff who work in ICU were invited to answer questionnaire to assess their knowledge, attitude, and practices related to nutrition care. Results: Showed that from 87 personal of medical staff in ICUs. Gander and place of work had a significant correlation with their knowledge (p-value=0.049 and p-value=0.007, respectively). Medical staff attitude had no significant correlation. medical staff knowledge/attitude had a significant relationship with Gander and place of work (p-value=0.025 and p-value=0.055, respectively). medical staff practice had a significant relationship with education level and job title (p-value=0.029 and p-value=0.018, respectively). medical staff knowledge and attitude/practice had a significant relationship with Gander (p-value=0.024). Conclusions: Findings demonstrate that respondents in Taiz, Yemen, had low nutritional KAP scores, indicating inadequate knowledge hindering effective nutrition care in ICUs. High-quality documentation and nutrition knowledge are crucial for improving ICU nutrition practice.